Laser cutting of CFRP by Quasi-Continuous Wave (QCW) fibre laser: Effect of process parameters and analysis of the HAZ index. (1st November 2021) - Leone, C.; Mingione, E.; Genna, S.
Abstract: In the present work, laser cutting of Carbon Fibre Reinforced Plastics (CFRP) is investigated by means of a Quasi Continuous Wave (QCW) fibre laser. The adoption of high pulse power (up to 4.5 kW) and short pulse duration (0.05 ms) may reduce the HAZ formation and allows high cutting speed. For the aforementioned reasons, the improvement of the laser cutting parameters is industrially relevant, especially on materials that are difficult to cut with the standard modes. To assess the influence of the process parameters on kerf geometry and Heat Affected Zone, experimental tests were carried out fixing the average power at 450W and changing the pulse power, the pulse duration, and the overlapping factor. The tests were performed adopting a full factorial design 3 3 according to the DoE methodology. ANalysis Of VAriance was used to determine which and how the process parameters affect the kerf geometry and HAZ extension. Results show that the laser allows cutting 1.3 mm-thick CFRP sheets with cutting speed up to 2700 mm/min. Also, by an appropriate selection of the process parameters, it is possible to obtain narrow kerfs (smaller than 200 μm) and a limited HAZ (about 0.5 mm). Besides, the correlation between the inner and the outer HAZ was found: the HAZ measured on the bottom surface can be usefully adopted as a damage index to understand the overall thermal damage since it can be correlated to section HAZ. The latter is the reference damage parameter according to UNI EN ISO 12584 standard.